Macroeconomic Effects of Japan's Demographics : Can Structural Reforms Reverse Them? - Colacelli, Mariana (IMF Working Papers; Working Paper, 2018)
Yes, partly. This paper studies the potential role of structural reforms in improving Japan's outlook using the IMF's Global Integrated Monetary and Fiscal Model (GIMF) with newly-added demographic features. Implementation of a not-fully-believed path of structural reforms can significantly offset the adverse effect of Japan's demographic headwinds - a declining and ageing population - on real GDP (by about 15 percent in the next 40 years), but would not boost inflation or contribute substantially to stabilizing public debt. Alternatively, implementation of a fully-credible structural reform program can contribute significantly to stabilizing public debt because of the resulting increase in inflation towards the Bank of Japan's target, while achieving the same positive long-run effects on real GDP. If no reforms are implemented, severe demographic headwinds are expected to reduce Japan's real GDP by over 25 percent in the next 40 years.